PENGARUH CENDAWAN Trichoderma sp. TERHADAP TANAMAN TOMAT PADA TANAH ANDISOL - Subhan Subhan; Nono Sutrisno; Rahmat Sutarya (BERITA BIOLOGI, 2012)
An experiment to determine the effect of Trichoderma fungus application in tomato grown in andisol soil, was conducted at IVEGRI’s (Indonesian Vegetable Research Institute) Experimental Garden in Lembang, Bandung, West Java (1250 m asl) from April 2011 until July 10 2011. Two treatments factos i.e. factor (1) Trichoderma application (without and using Trichoderma 10 fungi per plot and factor (2) NPK (15-15-15) fertilizer rate (0, 250, 500, 750 and 1000 kg NPK (15-15-15)/ha) were arranged in randomized block design with 4 replications. The results showed that although P uptake in tomato increased with Trichoderma sp. application, in general Trichoderma sp. application did not significantly affected several growth parameters and yield component of tomato. Significant effect of Trichoderma sp. application was only increased in total plant dry weight at 63 days after planting. The use of NPK (15-15-15) fertilizer 250 kg NPK/ha increased significantly on total plant dry weight and yield component such as total fruit weight per plot and fruit number per plot (15 m ).